The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/jp0553535
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Investigation of Eu(III) Complexes with β-Diketonates and Phosphine Oxides:  Model Complexes of Fluorescence Compounds for Ultraviolet LED Devices

Abstract: The density functional theory was employed to investigate Eu(III) complexes with three beta-diketonates and two phosphine oxides (complex M1: Eu(bdk)3(TPPO)2, complex M2: Eu(bdk)3(TMPO)2, and complex M3: Eu(bdk)3(TPPO)(TMPO)) deemed to be the model complexes of the fluorescence compounds for the ultraviolet LED devices we have recently developed. For each complex, two minimum energy points corresponding to two different optimized geometries (structures A and B) have been found, and the difference of the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 28 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…E x_t can be obtained by the energy difference between the lowest triplet and singlet state at the optimized ground-state geometry. 26 While E ET can be obtained from two pathways previously reported by Aigo: 26,27 one is the energy difference between E x_t and emission energy of Eu 3+ from 5 D 0 to 7 F 2 (E ET1 ), and the other is the excitation energy difference between the first singlet excited state and the first triplet excited state calculated by TDDFT (E ET2 ). In addition, Aigo suggested that the singlet to triplet intersystem crossing energy (E ISC ) is calculated with the excitation energy difference between the first singlet excited state and the first triplet excited state by TDDFT calculation.…”
Section: Energy-transfer Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…E x_t can be obtained by the energy difference between the lowest triplet and singlet state at the optimized ground-state geometry. 26 While E ET can be obtained from two pathways previously reported by Aigo: 26,27 one is the energy difference between E x_t and emission energy of Eu 3+ from 5 D 0 to 7 F 2 (E ET1 ), and the other is the excitation energy difference between the first singlet excited state and the first triplet excited state calculated by TDDFT (E ET2 ). In addition, Aigo suggested that the singlet to triplet intersystem crossing energy (E ISC ) is calculated with the excitation energy difference between the first singlet excited state and the first triplet excited state by TDDFT calculation.…”
Section: Energy-transfer Mechanismmentioning
confidence: 99%
“…In addition, Aigo suggested that the singlet to triplet intersystem crossing energy (E ISC ) is calculated with the excitation energy difference between the first singlet excited state and the first triplet excited state by TDDFT calculation. 27 To have efficient sensitization, an empirical rule indicates that E ET must be larger than 0.43 and E ISC must be larger than 0.62 eV. 28 For E x_t values in Table 2, Eu-Phen, Eu-PyPhen and Eu-MPP have the similar values of about 2.5 eV, and they are about 2.3 eV for other complexes, with the exception of Eu-BDPz, which is especially small in comparison with others (1.51 eV).…”
Section: Energy-transfer Mechanismmentioning
confidence: 99%
“…In addition, the intersystem crossing energy (DE ISC ) is the energy difference between the first singlet excited state (S 1 ) and the first triplet excited state (T 1 ) [32]. The DE ISC can estimate the probability of intersystem conversion.…”
Section: The Absorption and Emission Spectramentioning
confidence: 99%
“…Two minimum energy points corresponding to two different optimized geometries (structures A and B) have been found, and the difference between two minimum energy points is small (less than 1 kcal/mol). From these results, it is known that structures A and B can both exist in a solution or a polymer [33]. Time-dependent density functional theory (TDDFT) calculations suggest that the absorption coefficient of structure A is larger than that of structure B, resulting in a larger emission intensity.…”
Section: Molecular Designs Properties and Molecular Structures Ofmentioning
confidence: 99%